Pendampingan Guru dalam Pembuatan Media Pembelajaran Interaktif Berbasis Canva - Pixyoriza Pixyoriza; Erni Mariana; Sulis Anjarwati; Uswatun Khasanah (Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital technology requires teachers to be competent in developing interactive, innovative learning media that meet the needs of 21st-century learning. However, teachers' use of digital technology still faces various obstacles, particularly in creating engaging learning media. This community service activity aims to improve teachers' competency in developing interactive learning media based on Canva. The activity was carried out in Tanjung Qencono Village and involved 15 teachers from the educators community. The methods used included participatory training and direct mentoring through the stages of needs analysis, preparation, training, mentoring, and evaluation. Evaluation was conducted using a participant response questionnaire. The results of the activity showed that most participants understood the concept of interactive learning media and were able to operate Canva's features independently. Furthermore, teachers' media design skills and creativity also improved, accompanied by a very high level of participant satisfaction. Thus, this mentoring activity was effective in improving teachers' digital competency and encouraging the development of more creative, interactive, and relevant learning media to meet learning needs.